2013
DOI: 10.1175/jcli-d-13-00263.1
|View full text |Cite
|
Sign up to set email alerts
|

Circulation, Moisture, and Precipitation Relationships along the South Pacific Convergence Zone in Reanalyses and CMIP5 Models

Abstract: One theorized control on the position of the South Pacific convergence zone (SPCZ) is the amount of low-level inflow from the relatively dry southeastern Pacific basin. Building on an analysis of observed SPCZ region synoptic-scale variability by Lintner and Neelin, composite analysis is performed here on two reanalysis products as well as output from 17 models in phase 5 of the Coupled Model Intercomparison Project (CMIP5). Using low-level zonal wind as a compositing index, it is shown that the CMIP5 ensemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…Niznik and Lintner (2013) showed that synoptic time scale changes to low-level inflow east of the SPCZ in coupled GCMs are associated with spatial shifts in precipitation consistent with observations, albeit with considerable intermodel spread in the spatial distributions of these shifts. These results implicate potential connections between low-level inflow variability and the frequency with which synoptic disturbances interact with the SPCZ.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Niznik and Lintner (2013) showed that synoptic time scale changes to low-level inflow east of the SPCZ in coupled GCMs are associated with spatial shifts in precipitation consistent with observations, albeit with considerable intermodel spread in the spatial distributions of these shifts. These results implicate potential connections between low-level inflow variability and the frequency with which synoptic disturbances interact with the SPCZ.…”
Section: Introductionsupporting
confidence: 72%
“…As a basis for comparison in the relatively data-sparse South Pacific, the National Centers for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR; Saha et al 2010) is used in all analyses during the 32-yr period spanning 1979-2010 (variables examined in the CMIP5 models are also available for CFSR during this period). Niznik and Lintner (2013) showed that CFSR captures the climatological position of the SPCZ well (cf. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonality in surface convergence also contributed to the region of enhanced seasonal variability in the subtropical western south Pacific. The South Pacific Convergence Zone (SPCZ) lies within this region, and the orientation and intensity of the SPCZ vary on synoptic through to interannual timescales (e.g., Matthews, 2012;Niznik and Lintner, 2013). This variability in the SPCZ then results in variability in tracer ages; e.g., when the SPCZ is shifted to the northeast from its climatological there is less rapid transport from the NH and more from SH middle latitudes, resulting in older ages.…”
Section: Seasonal Variabilitymentioning
confidence: 99%
“…Extensive assessment studies have reported that most reanalyses display a certain level of performance in terms of their absolute values (Betts et al, 1996(Betts et al, , 1998Zhou and Wang, 2016b), interannual variability (Lin et al, 2014;Lindsay et al, 2014;Wang, 2016a, 2017a;Wang and Zeng, 2012), distributions (Gervais et al, 2014;Heng et al, 2014;Mao et al, 2010) and relationships among variables (Niznik and Lintner, 2013;Cash III et al, 2015;Zhou et al, 2017;Zhou and Wang, 2016b;Betts, 2004) over regions worldwide. However, these aspects of reanalyses still contain certain errors that restrict the general use of reanalyses, especially in climate applications.…”
Section: Introductionmentioning
confidence: 99%